A Study on Ductilization of Titanium Aluminides at Elevated Temperatures - Han, Chang-Suk (Asian Journal of Chemistry, 2015)
The effect of slight exposures in air on the ductility of TiAl and Super a2 was studied. It was found that embrittlement occurred only in the low-temperature range where they fracture by transgranular cleavage with low ductilities. The ductility decreased to 0.3 % from the original values of 1 and 2.2 % for TiAl and Super a2, respectively. The minimum ductility was obtained after a short-term oxidation. Numerous steps, probably due to twins and slips, were observed at the bent surface. The ratio of cracked to uncracked steps was large in severely embrittled specimens. It was concluded that the formation of cracked steps due to a thin oxide film has brought about the premature fracture.